Mutual facilitation between foundation species Mytilus edulis and Lanice conchilega promotes habitat heterogeneity on tidal flats - Nauta, Janne; Meijer, Kasper J.; de Groot, Lissie W.; Reijers, Valérie C.; Bouma, Tjeerd J.; van der Wal, Daphne; Olff, Han; Holthuijsen, Sander J.; Bijleveld, Allert I.; van der Veer, Henk W.; Franken, Oscar; Govers, Laura L. (Frontiers in Marine Science, 2024)
Foundation species that modify their habitat can facilitate other species, including other foundation species. Most studies focus solely on a single foundation species, overlooking such facilitation cascades. In this study, we investigated the interactions between the two coastal foundation species Mytilus edulis (blue mussel) and Lanice conchilega (sand mason worm). We investigated whether these species engage in facilitative interactions or if their association simply reflects a shared ecological niche on the soft-sediment intertidal flats of the Dutch Wadden Sea. To do so, we performed species distribution modeling, manipulative field experiments, and field surveys. We found a positive association between both foundation species, with a 2.45 times higher occurrence of both species compared to a random distribution. In addition, these species partially occupied the same ecological niche. We demonstrated that L. conchilega provided settlement substrate for M. edulis spat, increasing densities by 400 times compared to bare plots. Furthermore, M. edulis reefs facilitated L. conchilega occurrence in the wake of the reef. Biogenic reef development revealed that this interspecific facilitation resulted in spatial habitat heterogeneity. Therefore, we conclude that interspecific facilitation can significantly enhance the occurrence of these two important intertidal foundation species. Acknowledgment of such complex facilitation interactions has an untapped potential for improving the success of restoration and conservation programs.